Lorentz Forces And Nano Particle Shapes On Water, Ethylene Glycol And Engine Oil Based Cu, Al2o3 And Swcnts - Adnan, Nur Atikah; Aman, Fazlina; Kandasamy, R. (Institute of Advanced Scientific Research, 2020)
This paper investigates the effect of nanoparticle shapes on MHD water, ethylene glycol, engine oil based Cu, Al2O3 and SWCNTs over a stretched plate includes concern of thermal radiation. The aim is to examine the influence of various nanoparticle shapes such as sphere, cylinder and lamina on the performance of heat transfer in the presence of water, ethylene glycol, engine oil based Cu, Al2O3 and SWCNTs by using numerical approach. Similarity transformation is used to transform the governing partial differential equations (PDEs) into ordinary differential equations (ODEs) which then are analyzed numerically by shooting technique coupled with Runge Kutta Fehlberg method in MAPLE18 software. Simultaneous effects of magnetic, velocity ratio parameter, radiation, temperature index and volume fraction of nanoparticle are demonstrated graphically. Analysis of nanoparticle shapes reveal that sphere shape plays a dominant role to enhance rate of heat transfer and increase temperature distribution of nanofluid with enhancing of magnetic, thermal radiation, volume fraction while temperature distribution reduces with increasing of velocity ratio and temperature index values.